PROBLEMS WITH REDUCED BONE DENSITY IN SYSTEMIC SCLERODERMA - Sevara M. Mukhammadieva; Alibek A. Khudoynazarov (Central Asian Journal of Medicine, 2023)
Systemic scleroderma (SSD) is a chronic progressive connective tissue disease with an unknown etiology and clinically heterogeneous manifestations. It is based on 3 pathological processes: vasculopathy, cellular and humoral autoimmune condition and progressive visceral and vascular fibrosis in many organs. SSD disease is a reduction in the synthesis and accumulation of collagen in the skin (scleroderma) and other internal organs, especially in the connective tissue of the lungs, gastrointestinal tract (gastrointestinal tract), heart and kidneys. Vitamin D deficiency causes disturbance of calcium homeostasis and bone metabolism. Vitamin D deficiency leads to hyperthyroidism, bone loss and fractures. The article focuses on the importance of vitamin D in reducing bone density in patients with SSD and its early assessment.